Changing Prevalence of Helicobacter pylori Infections in Korean Children with Recurrent Abdominal Pain - Jang, Kyung Mi (Pediatr Gastroenterol Hepatol Nutr, 2015)
PURPOSE: The aim of this study is to investigate the changing prevalence rate of Helicobacter pylori infection in children, of different age groups, with recurrent abdominal pain over a 10-year period. METHODS: Children with recurrent abdominal pain who visited the pediatric outpatient clinic at university hospital were screened for H. pylori. Children were divided into 3 age categories of 4-5, 6-11, and 12-16 years. To study the changes in the annual prevalence rates of H. pylori infection, the study period was divided into 3 time periods: 2004-2007, 2008-2010, and 2011-2014. Urea breath test was performed for all children aged 4-16 years, with a cut-off value of 4.0‰ for children aged ≥6 years and 7‰ for children aged <6 years. RESULTS: A total of 2,530 children (1,191 boys) with a mean age of 10.0±3.0 years (range, 4.0-16.9 years) were included in the study. The total prevalence of H. pylori infection was 7.4% (187/2,530). The prevalence rate of H. pylori infection in children with recurrent abdominal pain was 8.0% (70/873) in 2004-2007, 7.7% (51/666) in 2008-2010, and 6.7% (66/991) in the 2011-2014. Nevertheless, a significant difference was observed in the prevalence rate between children <12 years old and ≥12 years of age (p=0.018). CONCLUSION: The prevalence of H. pylori infection in Korean children with recurrent abdominal pain was 7.4%, showing no significant decrease in the last 11 years; however, the prevalence rate in children <12 years old was significantly lower than that in those ≥12 years old.